Infiltration Kinetics of Wetting in a Building Plaster and the Effect of Added Glass and Hemp Fibers. (6th March 2013) - Gassita, Serge; Marmoret, Laurent; Perwuelz, Anne; Beji, Hassen
Abstract : Capillary rise is an important cause of deterioration for plaster in building. This phenomenon has been studied by the tensiometric experimental technique. Structural and hydric characteristics of plaster have been determined. Decane, a perfectly impregnate fluid, has been used to calculate the porous constant characteristic called C m and other structural parameters like pore radius and specific surface. Evaluation of the sensibility of plaster for water has been evaluated in a second time. The angle constant and the capillary moisture content have been determined. A comparison between results for plaster and composite plaster with fiber has been done. The addition of glass and hemp fiber does not have important effect on hydric properties (angle constant), but we have observed influence on structural charecteristics (pore radius, porosity, and degree of heterogeneity).